1.57 Ga protolith age of the Neoproterozoic Forquilha eclogites, Borborema Province, NE-Brazil, constrained by U–Pb, Hf and Nd isotopes. (March 2015) - Amaral, Wagner; Santos, Ticiano José; Ancelmi, Matheus Fernando; Fuck, Reinhardt Adolfo; Dantas, Elton Luiz; Matteini, Massimo; Moreto, Carolina Penteado
Abstract: The 30 km-long, N–S-trending Forquilha eclogite zone, occurs within a Paleoproterozoic block mainly composed of gneisses and migmatites, in the Ceará Central domain, Borborema Province, NE Brazil. The Forquilha eclogite zone contains lenses of high to ultra-high pressure metamafic rocks, found as granulites and amphibolites associated with kyanite-sillimanite gneisses. Three samples of clinopyroxene-garnet amphibolite yielded the U–Pb zircon ages of 1566 ± 9 Ma, 1547 ± 37 Ma and 1532 ± 24 Ma, interpreted as the timing of igneous crystallization of the mafic protolith. Additionally, zircon grains of a leucocratic layer of a metamafic rock and a retrograded eclogite provided the less precise U–Pb ages of 1613 ± 40 Ma and 1454 ± 120 Ma, respectively. Lu–Hf and Sm–Nd model ages provided TDM (Hf) between 1.55 and 1.81 Ga with positive εHf values of +7.50 to +10.48, and TDM (Nd) ranging between 1.57 and 1.92 Ga with positive εNd values of +1.84 to +4.36. It is believed that part of the rocks of the Forquilha eclogite zone were emplaced as mafic dikes in an extensional setting at ca . 1.57 Ga. Highlights: 1.57 Ga protolith age of the metamafic rocks of the Forquilha eclogite. These metamafic rocks were emplaced in an extensional setting. The metamorphism that affected these rocks was related to the Brasiliano/Pan-African orogeny.